Bioaccumulation of UV filters in Mytilus galloprovincialis mussel. (January 2018) - Vidal-Liñán, Leticia; Villaverde-de-Sáa, Eugenia; Rodil, Rosario; Quintana, José Benito; Beiras, Ricardo
Abstract: In this study the bioaccumulation kinetics of organic UV filters, such as 4-MBC, BP-3, BP-4, OC and OD-PABA in wild Mytilus galloprovincialis mussels was investigated. The uptake and accumulation of waterborne 4-MBC, BP-4 and OC was very rapid, and after only 24 h of exposure to 1 μg L −1, the tissular concentrations were 418, 263 and 327 μg kg −1 d.w., respectively. The kinetics of bioaccumulation of BP-4 and OC significantly fitted to an asymptotic model with BCF values of 905 L kg −1 and 2210 L kg −1, respectively. Measured bioaccumulation of the hydrophilic chemical BP-4 was much higher than predicted by Kow -based bioconcentration models, which would lead to a marked underestimation of actual risk. On the other hand, the patterns of uptake found for BP-3 and OD-PABA suggest biotransformation ability of mussels for these two chemicals. Highlights: The uptake of waterborne 4-MBC, BP-4 and OC was very rapid after only 24 h of exposure to 1 μ L −1 . Bioconcentration factor (BCF) was calculated for OC and BP-4. BP-3 showed a low accumulation in marine mussels. OD-PABA not tends to accumulate in biota due to their high capacity for elimination in mussels.